How much has benefited Romania from ten years of EU membership? - Constantin Zaman; Bogdan Meunier (Agora International Journal of Economical Sciences (AIJES), 2016)
We analyse in this paper the main achievements of Romania during the period of ten years since joining the European Union. The analysis is based on a proposed Index of Structural Changes constructed that express the overall progress in five areas: business environment, labour market, state institutions, taxation, and human capital. The analysis is carried out in a comparative perspective, at three levels: with Bulgaria, which joined the EU the same year; with three countries from Western Europe; and with a group of countries from Central and Eastern Europe that integrated the EU earlier, in 2004. We find a strong convergence between Romania and the other neighbouring countries, as well as a slower but increasing convergence towards the "old" EU member states.
Keywords: 330